FIB-4 and APRI scores for progressive liver fibrosis diagnosis in children with biliary atresia - Lyu, Hongyu; Ye, Yongqin; Wang, Bin (Frontiers in Pediatrics, 2024)
Introduction Finding non-invasive methods to predict the degree of liver fibrosis is very important in managing children with biliary atresia. Therefore, we explored the predictive value of APRI, FIB-4, and serological markers for liver fibrosis in children with biliary atresia. Methods This study retrospectively reviewed data from children diagnosed with BA between March and December 2022. Liver tissue pathology specimens were obtained during surgery. The serum markers were measured within 2 days before the Kasai procedure or liver transplantation. The aspartate aminotransferase-to-platelet ratio index (APRI) and the four-factor-based fibrosis index (FIB-4) were calculated. The outcome was the diagnosis of progressive liver fibrosis. Results This study reviewed the data from 41 children with biliary atresia. APRI had 52% sensitivity and 83% specificity for progressive liver fibrosis, while FIB-4 had 83% sensitivity and 67% specificity. Their areas under the curve were not significantly different from those of conventional markers. Conclusion Although they were not better than conventional markers, APRI and FIB-4 can be used as follow-up markers for progressive liver fibrosis in patients with biliary atresia, but their predictive value was moderate. Additional studies are necessary to determine whether they could be combined with other markers to improve their predictive value.